2022
DOI: 10.1186/s12877-022-03520-7
|View full text |Cite
|
Sign up to set email alerts
|

The identification and prediction of frailty based on Bayesian network analysis in a community-dwelling older population

Abstract: Background We have witnessed frailty, which characterized by a decline in physiological reserves, become a major public health issue in older adults. Understanding the influential factors associated with frailty may help prevent or if possible reverse frailty. The present study aimed to investigate factors associated with frailty status and frailty transition in a community-dwelling older population. Methods A prospective cohort study on community-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Participants who were classified as robust or pre‐frailty in 2020 and whose frailty status worsened by at least one level in 2022, as well as those who were classified as frailty in both 2020 and 2022, were assigned to the remained frail/deteriorated group ( n = 133), whereas all other participants were assigned to the non‐deteriorated group ( n = 416). These groupings were similar to those in previous studies 18,19 …”
Section: Methodssupporting
confidence: 92%
“…Participants who were classified as robust or pre‐frailty in 2020 and whose frailty status worsened by at least one level in 2022, as well as those who were classified as frailty in both 2020 and 2022, were assigned to the remained frail/deteriorated group ( n = 133), whereas all other participants were assigned to the non‐deteriorated group ( n = 416). These groupings were similar to those in previous studies 18,19 …”
Section: Methodssupporting
confidence: 92%
“…Blood lipids, such as triglycerides and LDL-C, play a significant role in the development of atherosclerosis, and research indicates that lowering these lipid levels can reduce the risk of cardiovascular diseases [ 35 ]. A Bayesian network analysis conducted on community-dwelling older people suggested that HDL-C levels may be associated with malnutrition and can have an impact on frailty status [ 36 ]. This finding aligns with the results of our reverse MR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Low HDL‐C and high LDL‐C levels are well‐known risk factors for cardiovascular diseases, whereas low serum cholesterol levels also indicate malnutrition 27 which is associated with frailty. 28 Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Low HDL-C and high LDL-C levels are well-known risk factors for cardiovascular diseases, whereas low serum cholesterol levels also indicate malnutrition 27 which is associated with frailty. 28 -9 of 13 demonstrated that low LDL-C level was a risk factor for frailty in older Japanese males with diabetes but not in females.…”
Section: Totalmentioning
confidence: 99%